Assessment of genetic diversity and population structure of swamp eel Monopterus albus in China. (October 2016) - Liang, Hongwei; Guo, Shanshan; Li, Zhong; Luo, Xiangzhong; Zou, Guiwei
Abstract: Swamp eel has become one of the most economically important fish in China. However, the wild swamp eel is facing the serious challenge of declining population and germplasm degeneration because most of farming swamp eel fingerlings was collected by fishing wild individuals. In this study, the genetic variation of Monopterus albus in six dominant farming regions was investigated based on the mitochondrial DNA D-Loop of 1008 bp in length. 180 individuals from 6 populations were examined and 74 haplotypes were observed. The overall genetic diversity was abundant and which its SD population was highest but CQ population was lowest. There was obvious genetic differentiation among investigated populations. Phylogenetic analysis revealed that these individuals were divided into four distinct genetic clades, clade A, B, C, and D. Clade A should be the most common ancestor clade. AH and CQ populations might originate from one single ancestor in maternal clade A. Clade C should be a native important clade in China. Though the genetic diversity did not suffered obvious decreasing, it is still imperative to take effective conservation measurements and establish an efficient selective breeding program. Highlights: Genetic diversity of six dominant farming regions. There was obvious genetic differentiation. Genetic diversity did not suffered obvious decreasing.